Edukasi Menstruasi Berbasis Syariah sebagai Metode Meningkatkan Perilaku Remaja Selama Menstruasi - Fadlilah Shofiyyuna; Sri Wahyuni; Apriliani Yulianti Wuriningsih (Pusat Riset dan Inovasi Nasional, 2025)
Menstruation is a sign that a woman has a uterus in her stomach, so menstruation is normal for all women. Sharia-based menstruation has differences in terms of cleansing (hygiene), counting the menstrual blood that comes out, prohibitions, and what is permitted during menstruation. This research is quantitative research, using Pre-Experimental Design with a Two Group Pretest-Posttest design. Sampling used a stratified random sampling technique, the number of respondents was 64 female students using the paired t-test. The results of the respondent analysis weare obtained from 32 respondents at SMA 3 Sultan Agung, on average there were 25 female students aged 17 years with a percentage of (78.1%). And it is known that of the 32 respondents at SMA 1 Sultan Agung, the average number of 17 year old female students was 22 respondents with a percentage of (66.7%). And the test results show that the level of knowledge of SMA 3 Sultan Agung female students increased significantly after receiving the intervention from (30.46%) to (86.87%). However, this is different from SMA 1 Sultan Agung, where there are only slight changes because there is no intervention. There is an influence of Sharia-based menstrual education on adolescent behavior during menstruation in high school with a p-value of 0.001 (p-value < 0.05)